2-{(E)-[(2-Hydroxy-1-phenylethyl)imino]methyl}-4-[(E)-(4-methylphenyl)diazenyl]phenol - Mohammad H. Ati; Basil A. Saleh; Adnan J. M. Al-Fartosy; Gamal A. El-Hiti; Benson M. Kariuki (IUCrData)
In the title compound, C22H21N3O2, an intramolecular O—H...N hydrogen bond is observed between the phenol and methanimine groups of the molecule. The 2-phenylethan-1-ol part is disordered over two orientations [occupancies 0.566 (17) and 0.434 (17)]. In the crystal, disordered intermolecular O—H...O hydrogen bonds between adjacent molecules form chains parallel to the b axis.